An impact of the state and type of surface layer on magnetic properties of Cu/Ni and Ni/Cu multilayers - Gągorowska, Barbara; Duś-Sitek, Marta; Nabiałek, Marcin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This paper presents the results of investigation of magnetic properties in Cu/Ni multilayer systems. Based on the investigation of Ni/Cu and Cu/Ni systems with different thickness of magnetic and non-magnetic layers it was proved that the presence of ferromagnetic (F-F) and antiferromagnetic (A-F) exchange couplings depends on the quality of layers in artificial superlattice and on the state and type of free surface, superlattice structure and its roughness.
Optica Applicata, Vol. 39, 2009, nr 4, s. 839-844
Keywords: optyka; multilayer systems; antiferromagnetic coupling; ferromagnetic coupling